Subdeltoid Bursa Tuberculosis with Rice Bodies Formation (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2016)
Introduction: We describe a rare case of a patient with unilateral musculoskeletal manifestation of tuberculosis presented as bursitis of the left shoulder with rice bodies, without coexisting active tuberculosis or tuberculosis in the previous history.Case Report: A 21 year old patient was examined, who complained of pain and swelling in the left shoulder for 2 years. MRI showed a large amount of rice bodies with joint effusion in the left shoulder with intact rotator cuff. The histological examination showed a tuberculosis-specific inflammatory response with giant cells and epithelioid granulomas. Arthroscopic debridement and removal of the loose bodies was done.Conclusion: We report a unique case of tuberculous sub-deltoid bursitis with rice bodies formation in absence of any other concomitant focus of tuberculous infection, managed with arthroscopic debridement and anti -tuberculous regimen with a long follow up of twelve months.SAARC J TUBER LUNG DIS HIV/AIDS, 2015; XII(2): 28-31